Comprehensive risk assessment and control measures in the food service chain of hospitals nutrition department: a case study in Al-Ahsa Governorate, Kingdom of Saudi Arabia - Saleh, Farag Ali; Mohamed, Hisham Abdelmonem; Munir, Muhammad; Al Otaibi, Mutlag Mohammad; Kamel, Sahar Mostafa; Alsaif, Omar Mohammed; Alqahtani, Abdulaziz Ali; AlDabal, Malak Abdullah (Frontiers in Microbiology, 2025)
IntroductionEnsuring hospital food safety is essential for patient health, infection control, and public trust. This study evaluates food exposure risks in two hospitals in Al-Ahsa Governorate, Saudi Arabia, focusing on critical control points during food processing and delivery.MethodsMicrobial analysis was conducted on food samples from various stages of food preparation, including raw meat, chicken, fish, and prepared meals. Temperature monitoring and chemical hazard assessments were also carried out, including pesticide residue and heavy metal analysis.ResultsThe microbial analysis detected specific pathogens, including Salmonella, Listeria monocytogenes, Escherichia coli, and Staphylococcus aureus, along with yeasts and molds. Total bacterial counts (TBC) in raw meat, chicken, and fish ranged from 2.5 to 5.0 log cfu/g, while prepared meals had TBCs between 1.0 and 3.0 log cfu/g. No Salmonella or Listeria monocytogenes were detected. Chemical hazards, including mycotoxins in white flour and heavy metals, were within permissible limits. However, 12 pesticides were detected, with six exceeding European Food Safety Organization limits.DiscussionTemperature monitoring revealed that hot foods cooled to unsafe levels during transport, and cold samples were not consistently maintained at SFDA-recommended temperatures. Hospitals generally comply with health regulations but improvements are necessary in temperature control and preventing chemical contamination of raw materials.